(3GdJehjd GdNGQLj h SjGSGJ GdGUdGM GdGbJUGOj (B:s (3JLGQH YQHjI (B/s - (3jhfS, YOfGf MSjfs ((3YeGf(B: s (3OGQ GdefGgL ddfTQ hGdJhRjY(B, s, 2011)
(3GdGWGQ GdeaGgjej ddJehjd GdNGQLj ef GdHdOGf GdfGejI, GdJehjd GdNGQLj ddHdOGf GdfGejI cGMOi BdjGJ GdJUMjM aj GdGbJUGO GdQCSeGdj, GdJehjd GdNGQLj h YdGbJg HSjGSGJ GdGUdGM GdGbJUGOj aj GdHdOGf GdfGejI, GdbQGV GdNGQLjI deUQ h GdGQOf h JhfS aj Xd SjGSGJ GdGUdGM GdGbJUGOj, OhQ GdGSJKeGQGJ GdGLfHjI aj GdJehjd GdNGQLj aj HdOGf GdGUdGM GdYQHjI, BKGQ GdJehjd GdNGQLj h GdGUdGM aj HYV GdeJZjQGJ GdGbJUGOjI h GdGLJeGYjI aj cd ef eUQ, GdGQOf h JhfSs
Keywords: (3GdJNWjW GdEbJUGOjs; (3GdJehjd GdOhdjs; (3GdOjhf GdNGQLjIs